Peningkatan Motivasi Belajar Matematika melalui Pembelajaran Berbasis Masalah dengan Pendekatan Culturally Responsive Teaching pada Peserta Didik X-D SMAN 3 Tuban - Laksana, Fadhil (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2023)
This research aims to enhance the learning motivation of mathematics in the topic of statistics through problem-based learning with a culturally responsive teaching approach among the 10th-grade students of Class X-D at SMA Negeri 3 Tuban in the academic year 2022/2023. This study was conducted due to the findings that mathematics learning was challenging and lacked real-life relevance, coupled with low learning motivation among the students in statistics. A classroom action research was conducted with the research subjects being the 10th-grade students of Class X-D at SMA Negeri 3 Tuban. Data were collected through learning motivation questionnaires, observations, and interviews. The results of the study indicated that problem-based learning with a culturally responsive teaching approach could enhance the learning motivation of students in statistics. Therefore, problem-based learning with a culturally responsive teaching approach could be considered an alternative to improve learning motivation and student interaction in the statistics topic.